2011
DOI: 10.1007/s11250-011-0044-6
|View full text |Cite
|
Sign up to set email alerts
|

Multivariate analysis of sexual size dimorphism in local turkeys (Meleagris gallopavo) in Nigeria

Abstract: Sexual size dimorphism is a key evolutionary feature that can lead to important biological insights. To improve methods of sexing live birds in the field, we assessed sexual size dimorphism in Nigerian local turkeys (Meleagris gallopavo) using multivariate techniques. Measurements were taken on 125 twenty-week-old birds reared under the intensive management system. The body parameters measured were body weight, body length, breast girth, thigh length, shank length, keel length, wing length and wing span. Univa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
3
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 30 publications
3
3
0
2
Order By: Relevance
“…Most researchers consider an organism’s phenotype as a multivariate set of variables and the covariation of traits an important analytical consideration [22]. Discriminant analysis of morphometric traits is a mathematical approach that has been widely used in determining the relationships between different breeds of livestock [6,23-25]. The most discriminating variables obtained in this study are similar to previous reports by Dossa et al [16] and Vargas et al [26].…”
Section: Discussionsupporting
confidence: 84%
“…Most researchers consider an organism’s phenotype as a multivariate set of variables and the covariation of traits an important analytical consideration [22]. Discriminant analysis of morphometric traits is a mathematical approach that has been widely used in determining the relationships between different breeds of livestock [6,23-25]. The most discriminating variables obtained in this study are similar to previous reports by Dossa et al [16] and Vargas et al [26].…”
Section: Discussionsupporting
confidence: 84%
“…As for males, the third axis had a high contribution of beak length, which also represented an opposite direction between beak and wattle length. The present findings are consistent with the literature, in which general size is generally reported as the main factor of variation and thus constitutive of the first axis of PCA in chickens, rabbits, or turkeys (Shahin and Hassan, 2000;Ajayi et al, 2011;Egena et al, 2014). The principal component analysis allowed for better understanding of the complex correlations among the traits and reduced the number of traits, using only the three first PCs, without loss of information.…”
Section: Principal Components Analysissupporting
confidence: 93%
“…The present findings are consistent with the report of Gois et al (2012) where male body weight and body measurements were found to be higher than those of females showing dimorphism in the domestic duck of Brazil. Similar findings had been reported by earlier workers in ducks (Teguia et al 2008;Yakubu 2011) and other poultry species (Ajayi et al 2012), suggesting that sexual dimorphism in ducks is manifested with respect to a large number of body attributes and in most breeds. This may be attributed to sex hormones which may promote larger muscle development in males than in females (Guni et al 2013).…”
Section: Coefficient Of Determinationsupporting
confidence: 90%